2002
DOI: 10.1034/j.1600-6143.2002.20703.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Bile Production during Normothermic Preservation of Porcine Livers

Abstract: Machine perfusion of livers may provide a mechanism for extended preservation of marginal donor organs before transplantation, as well as a method for viability assessment. It has proved possible in a series of experimental porcine liver perfusions to maintain liver viability for up to 72 h. However, a reduction in bile production with associated histological evidence of cholestasis was seen after 10 h of perfusion, damaging the biliary canaliculi during the preservation period and leaving these organs in an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 15 publications
3
55
1
Order By: Relevance
“…Consistent with reports from previous studies and that from our laboratory [11,22,23], it was found that HMP significantly improves hepatic parenchymal enzyme release and functional recovery upon reperfusion. Beyond this, we could provide evidence that oxygenation during ex vivo storage by machine perfusion with either preservation medium significantly improved mitochondrial integrity, compared to simple CS, and largely attenuated cleavage of caspase 9, hallmark of the initiation of the intrinsic pathway of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with reports from previous studies and that from our laboratory [11,22,23], it was found that HMP significantly improves hepatic parenchymal enzyme release and functional recovery upon reperfusion. Beyond this, we could provide evidence that oxygenation during ex vivo storage by machine perfusion with either preservation medium significantly improved mitochondrial integrity, compared to simple CS, and largely attenuated cleavage of caspase 9, hallmark of the initiation of the intrinsic pathway of apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21). The same group recently introduced NMP in human liver transplantation using blood and additives during perfusion (18).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we do not believe the addition of bile salts is necessary when livers are perfused for less than 10 hours. In fact, hydrophobic bile salts have been demonstrated to play a role in bile duct epithelial injury after liver transplantation and this could be considered an additional argument not to add bile salts to the perfusion fluid [19], [20], [21], [22]. On the other hand, due to the strong choleric effect of bile salts, bile production during ex vivo NMP will be higher when bile salts are added to the perfusion fluid.…”
Section: Discussionmentioning
confidence: 99%